Genomic diversity of antimicrobial resistance in non-typhoidal Salmonella in Victoria, Australia. Issue 12 (15th December 2021) - Sia, Cheryll M.; Baines, Sarah L.; Valcanis, Mary; Lee, Darren Y. J.; Gonçalves da Silva, Anders; Ballard, Susan A.; Easton, Marion; Seemann, Torsten; Howden, Benjamin P.; Ingle, Danielle J.; Williamson, Deborah A.
Abstract : Non-typhoidal Salmonella (NTS) is the second most common cause of foodborne bacterial gastroenteritis in Australia with antimicrobial resistance (AMR) increasing in recent years. Whole-genome sequencing (WGS) provides opportunities for in silico detection of AMR determinants. The objectives of this study were two-fold: (1) establish the utility of WGS analyses for inferring phenotypic resistance in NTS, and (2) explore clinically relevant genotypic AMR profiles to third generation cephalosporins (3GC) in NTS lineages. The concordance of 2490 NTS isolates with matched WGS and phenotypic susceptibility data against 13 clinically relevant antimicrobials was explored. In silico serovar prediction and typing was performed on assembled reads and interrogated for known AMR determinants. The surrounding genomic context, plasmid determinants and co-occurring AMR patterns were further investigated for multidrug resistant serovars harbouring bla CMY-2, bla CTX-M-55 or bla CTX-M-65 . Our data demonstrated a high correlation between WGS and phenotypic susceptibility testing. Phenotypic-genotypic concordance was observed between 2440/2490 (98.0 %) isolates, with overall sensitivity and specificity rates >98 % and positive and negative predictive values >97 %. The most common AMR determinants were bla TEM-1, sul2, tet (A), strA-strB and floR . Phenotypic resistance to cefotaxime and azithromycin was low and observed in 6.2 % (151/2486) and 0.9 % (16/1834) of the isolates, respectively. Several multi-drug resistant NTS lineages were resistant to 3GC due to different genetic mechanisms including bla CMY-2, bla CTX-M-55 or bla CTX-M-65 . This study shows WGS can enhance existing AMR surveillance in NTS datasets routinely produced in public health laboratories to identify emerging AMR in NTS. These approaches will be critical for developing capacity to detect emerging public health threats such as resistance to 3GC.